Pengaruh Cadangan Kerugian Penurunan Nilai, Non-Performing Loans, dan Loan to Deposit Ratio Terhadap Profitabilitas pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Sososutiksno , Christina; Talabessy, Loudrik; Limba, Franco Benony (Politeknik Raflesia Press, 2024)
One sector that has enormous power to influence a country's economy is the banking sector. The health of a bank can be seen by achieving profitability through the ROA ratio. The change in accounting standards towards PSAK 71, which is effective since January 1, 2020, requires banks to make reserves using the method of expecting future losses. This study aims to empirically examine the effect of Impairment Loss Reserves, Non-Performing Loans, and Loan to Deposit Ratio, on company profitability. Using multiple linear regression analysis, this research was conducted on banking sector companies listed on the Indonesia Stock Exchange in 2020 – 2022, obtained from the Company's financial statements, and the Financial Services Authority (OJK) website. Based on the results of the study, it is known that the Impairment Loss Reserve and Loan to Deposit Ratio have a positive and significant effect on banking profitability. Meanwhile, Non-Performing Loans have a negative and significant effect on the Company's profitability.